EFL Learners’ perceptions towards meta-cognitive strategy use in English language listening - Bidabadi, Farinaz Shirani; Hamidah Yamat (Penerbit UKM, 2013)
Most Iranian learners face several difficulties when they need to listen to recordings in English or their lecturers' speech in English because they do not know how to employ the listening skills and listening strategies to understand the texts. Therefore, the purpose of this case study was to explore how Iranian female freshman learners, who are learning English as a foreign language (EFL) at tertiary level, listen to English texts in classrooms and what are their perceptions towards the use of meta-cognitive processes and strategies while listening to English texts. 84 Iranian EFL female freshman university learners who are majoring in Teaching English as a Foreign Language (TEFL), in the west of Esfahan, Iran participated in this study. They are native speakers of Farsi/Persian aged 18. Based on the scores obtained from Oxford Placement Test (OPT), they are placed in intermediate proficiency level category. The descriptive analysis of the four factors of Meta-cognitive Awareness Listening Strategies (planning and evaluation, problem-solving, personal knowledge, and directed knowledge) reveals that the learners employ directed knowledge strategies more frequently, followed by planning and evaluating, problem-solving, and personal knowledge strategies respectively. Furthermore, analysis from the qualitative data also supported the use of these four key factors in the meta-cognitive strategies, which contributed to how EFL learners understand and listen to English texts. The study implies that meta-cognitive strategies should be explicitly infused in the teaching and learning of listening activities in the classrooms.